Predictive Value of Brachial Artery Reactivity in Sepsis - Walid Omar; Ahmed Mokhtar; Kamel Abdelaziz; Hatem Alazizi (Egyptian Journal of Critical Care Medicine, 2020)
Abstract Introduction Endothelial dysfunction plays a major role in the pathophysiology of septic shock and organ dysfunction, and has been suggested to be a predictor of mortality in sepsis. Ultrasound measurement of brachial artery reactivity indices in response to transient ischemia provides indirect estimates of endothelial dysfunction. The aim of this study was to assess whether brachial artery reactivity indices could be used for prognostic assessment of patients with sepsis or not. Methods Fifty patients with diagnosis of sepsis were subjected to flow-mediated dilatation (FMD) of brachial artery within 24 hours from ICU admission. Measurements were compared in sepsis survivors versus nonsurvivors and correlated with clinical severity scoring systems (acute physiology and chronic health evaluation II and sequential organ failure assessment scores). Another 30 volunteers without acute illness were taken as a control group to determine a normal reference range for FMD. Results Hyperemic velocity was significantly lower in sepsis group versus control group (71.77±18.67 versus 81.64±9.84, P=.003). FMD was significantly lower in sepsis group compared to control group (3.72±2.22 versus 5.29±1.74, P=.001). Change in velocity was significantly lower in sepsis group compared to control group (19.53±10.80 versus 31.25±6.72, P<.001). Twenty percent of enrolled patients died within 28 days of hospital admission. Change in velocity was significantly lower in nonsurvivors versus survivors (7.82±2.26 versus 22.45±10.08, P=.001). Change of velocity of 12 cm/cardiac cycle was the cut point in predicting mortality in sepsis with sensitivity of 89.7% and specificity of 100% with a total accuracy of 92% and area under the curve (AUC) of 0.936 (CI 0.866–1.0). Discussion Brachial artery hyperemic change in blood velocity was a noninvasive indicator of microvascular function that independently predicted mortality in sepsis. In contrast, brachial artery FMD was not associated with mortality in our sepsis cohort.